Investigation of archived accurate mass data in mass spectrometry. - Mesfer Mohamed Alamri (2010)
"This thesis presents an investigation of mass measurement accuracy in mass spectrometry using archived accurate mass measurement data obtained on different types of mass spectrometry instruments. A magnetic sector was used as the "gold standard" analyzer and other data obtained on electrospray ionization fitted with Orbitrap and a MALDI time-of-flight instrument. More than 4500 accurate masses were obtained from the EPSRC National Mass Spectrometry Service Centre at Swansea University using the above instrument types. Different ionization methods are available; each has its own characteristics. In this study the ionization techniques used are chemical ionization (Cl), electron ionization (El), electrospray ionization (ESI), fast-atom bombardment (FAB) and matrix-assisted laser desorption/ionization (MALDI). These mass analyzers have different attributes, including the mass range, resolution and mass accuracy. Mass measurement accuracies (MMAs) are reported for a number of preferred techniques. Statistical calculations were made using various software pack-ages such as SPSS, AccMass (house software), Origin, Easyfit and Excel add-ins. The data contains view outliers which can significantly affect the accuracy and precision of the data as well as affecting the underlying statistical distribution predicted."